Strategic and innovative pricing : price models for a digital economy /: price models for a digital economy. (2020) - Cöster, Mathias; Iveroth, Einar; Olve, Nils-Göran, 1947-; Petri, Carl-Johan; Westelius, Alf
No abstract available